RETINOBLASTOMA IN NWFP, PAKISTAN - Arif, Muhammad; Iqbal, Zafar; Islam, Zia -ul- (Journal of Ayub Medical College Abbottabad, 2009)
Background: Retinoblastoma is a malignant intraocular tumour of childhood, if not detected early, it results in loss of eye as well as life. The Objective was to study the pattern of presentation of Retinoblastoma in order to detect the disease at an earlier stage. It was conducted at Supra Regional Referral Centre for Retinoblastoma, Department of Ophthalmology, Khyber Teaching Hospital, Peshawar, Pakistan from 1st July 1999 to 30th September 2002. Methods: Seventy patients were registered and admitted for diagnostic evaluation. After initial interview a proforma was filled about history of disease. Examination under anaesthesia included indirect ophthalmoscopy with indentation. B-scan of the eye and CT scan of the Orbit was done when required. Results: Forty (57.14%) patients presented with Leukocoria; other presentation included hyphaema, strabismus, proptosis, 56.48% patients presented in stage VB (Rees Elsworth classification). Conclusion: Early detection through better understanding of presenting features of the disease and application of diagnostic skills can reduce the advanced stage of Retinoblastoma. Keywords: Retinoblastoma, Leukocoria, strabismus, proptosis, B-scan, Rees Elsworth classification